Alternative pest control methods for false codling moth, Thaumatotibia leucotreta (Lepidoptera : Tortricidae): exploring juvenile hormone analogs and entomopathogenic nematodes for integrated pest management - Viljoen, Nadia (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScConsEcol)--Stellenbosch University, 2023.